2002
DOI: 10.1007/s00330-002-1491-2
|View full text |Cite
|
Sign up to set email alerts
|

Spiral CT arthrography of the knee: technique and value in the assessment of internal derangement of the knee

Abstract: Computed tomography imaging has achieved excellent multiplanar capability and submillimeter spatial resolution due to the development of the spiral acquisition mode and multidetector row technology. Multidetector spiral CT arthrography (CTA) yields valuable information for the assessment of internal derangement of the joints. This article focuses on the value of spiral CTA of the knee in the assessment of the meniscus, anterior cruciate ligament, and hyaline cartilage lesions. Advantages and disadvantages of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(26 citation statements)
references
References 33 publications
0
25
0
1
Order By: Relevance
“…In our CTA, the amount of Gd chelate added to the diluted iodinated agent was too low to give a detectable increase of electron density [20]. We should take into account that the diagnostic information of CTA could be increased by the higher-quality multiplanar reconstructions with multidetector equipment [21,22], making CT really comparable with MR multiplanar imaging. Finally, if MR and CT acquisitions were coregistered, an image fusion postprocessing would superimpose the bone and calcium analysis of CT on the soft tissue contrast resolution of MR [23].…”
Section: Discussionementioning
confidence: 97%
See 1 more Smart Citation
“…In our CTA, the amount of Gd chelate added to the diluted iodinated agent was too low to give a detectable increase of electron density [20]. We should take into account that the diagnostic information of CTA could be increased by the higher-quality multiplanar reconstructions with multidetector equipment [21,22], making CT really comparable with MR multiplanar imaging. Finally, if MR and CT acquisitions were coregistered, an image fusion postprocessing would superimpose the bone and calcium analysis of CT on the soft tissue contrast resolution of MR [23].…”
Section: Discussionementioning
confidence: 97%
“…Ovviamente, dobbiamo considerare che l'informatività diagnostica dell'artro-TC potrebbe essere nettamente incrementata dall'elevata qualità delle ricostruzioni multiplanari ottenibili con apparecchiature TC multidetettore [21,22], rendendo in tal senso la TC realmente comparabile con l'imaging multiplanare a RM. Infine, qualora le immagini RM e TC siano coregistrate, un post-processing che fonda le due immagini potrebbe sommare la sensibilità della TC per l'osso e il calcio con la risoluzione di contrasto della RM per i tessuti molli [23].…”
Section: Discussionunclassified
“…2.4 ). Vande Berg et al ( 2002 ) found, in a study with spiral CTA of cadaver knees, a better correlation for grading articular surfaces between macroscopic examination and spiral CTA than with MR imaging. Other potential advantages of spiral CTA with respect to MR imaging are the short examination time, the availability at short notice (short waiting list), and the low sensitivity for and limited degree of imaging artifacts related to the presence of microscopic metallic debris which may hinder MR imaging studies.…”
Section: Ct Arthrographymentioning
confidence: 97%
“…Contrast media mixture used was 25% iodinated contrast media (Iomeron 250) and 1.25 mmol/L gadolinium contrast media (Dotarem 0.5 mmol/ml diluted to 1/400 dilution). 12 12-20 ml of this combined contrast media was injected followed by MDCTA and MRA.…”
Section: Methodsmentioning
confidence: 99%
“…5,[7][8][9] The use of MDCTA as a diagnostic method in various joints, including the shoulder, has been reported. 2,[10][11][12][13][14] The purpose of this study was to determine the utility of MDCTA in evaluation of lesions associated with shoulder instability and its comparison with MRA and arthroscopy, taking arthroscopy as gold standard. We hypothesized that MDCTA would be cost effective and comparable with MRA for assessing lesions in shoulder instability.…”
Section: Introductionmentioning
confidence: 99%